PENGELOLAAN KEUANGAN DAN ASET DESA DALAM UPAYA PENGUATAN KELEMBAGAAN PEMERINTAH DESA - Maulidiah, Sri (UIR PRESS, 2015)
Countryside ever get serious attention and is special the than various component socialize and governmental, so that various component socialize to feel important to do/conduct renewal of about countryside governance. Because during the time arrangement of about countryside united by into Code/Law of about Governance of Area assumed still a lot of there are various form of feebleness and insuffiency in arranging, carrying out and attitude of dynamics of countryside as well as assumed [by] not yet able to quicken countryside development. historically, existence of countryside in Indonesia there have before Negara Kesatuan Republik Indonesia ( NKRI) there is or formed, is such as those which expressed in Rationale of Clarification of Code/Law of Republic Of Indonesia of Number 6 Year 2014 about Countryside, that;